Rural project management : a handbook for students and practitioners - Austin, Vincent (Batsford LondonGB, 1984)
Discusses the management of agricultural and rural projects. Outlines principles and practices suitable for large and small scale operations whether nationally, locally, or individually run. Considers a wide range of activities that characterize rural agricultural or industrial projects. Reviews a wide range of managerial skills in planning, organization, materials, production, transport, marketing and finance.